Colors and Dynamics of a Near-Sun Orbital Asteroid Family: 2021 PH27 and 2025 GN1 - Scott S. Sheppard; Henry H. Hsieh; Petr Pokorný; David J. Tholen; Audrey Thirouin; Carlos Contreras; Marcelo D. Mora; Mauricio Martinez; Ivonne Toro (The Astrophysical Journal Letters, 2025)
We observed the dynamically similar near-Sun asteroids 2021 PH27 and 2025 GN1 for their optical colors. These objects have the lowest known semimajor axes of any asteroids. 2021 PH27 has the largest general relativistic effects of any known solar system object. The small semimajor axis and very close passage to the Sun suggest the extreme thermal and gravitational environment should highly modify these asteroids’ surfaces. From g ’-, r ’-, i ’-, and z ’-band imaging, we find the colors of 2021 PH27 ( ${g}^{{′} }-{r}^{{′} }=0.58± 0.02$ , ${r}^{{′} }-{i}^{{′} }=0.12± 0.02$ , and ${i}^{{′} }-{z}^{{′} }=-0.08± 0.05$ mag) to be between the two major asteroid types: the S and C classes. With a spectral slope of 6.8 ± 0.03 percent per 100 nm, 2021 PH27 is an X-type asteroid and requires albedo or spectral features to further identify its composition. We find the dynamically similar 2025 GN1 also has very similar colors ( ${g}^{{′} }-{r}^{{′} }=0.55± 0.06$ and ${r}^{{′} }-{i}^{{′} }=0.14± 0.04$ ) as 2021 PH27, suggesting these objects are fragments from a once larger parent asteroid or 2021 PH27 is shedding material. The colors are not blue like some other near-Sun asteroids such as 3200 Phaethon that have been interpreted to be from the loss of reddening substances from the extreme temperatures. There is no evidence of activity or a large amplitude period for 2021 PH27, whereas 2025 GN1 might have a more significant rotational light curve. 2025 GN1 may have a very close encounter or hit Venus in about 2300 yr and likely separated from 2021 PH27 in the last ∼10 kyr.